BIM Implication of Life Cycle Cost Analysis in Construction Project: A Systematic Review - Altaf, M. (Institute of Electrical and Electronics Engineers Inc., 2020)
In the construction industry, the policymakers tend toward economic sustainability. Whereas in the construction industry the associated future cost inflicts barriers on project sustainability. Therefore, Life Cycle Cost Analysis (LCCA) approach, which acts as an economic indicator has been considered for predicting the associated cost. While predicting the Life Cycle Cost (LCC), there exists inconsistency in the future data, thus an automation approach is required to minimize the variability in the cost prediction and analyse the LCC. The purpose of this systematic review is to spotlight on the implications of Building Information Modelling (BIM) which is an automated approach in performing LCCA. The relevant literature was extracted from the Scopus database. A total of 39 articles were extracted, afterward, Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) methodology is applied, and 24 articles are left for further interpretation. In the reviewed articles, the importance of BIM in measuring LCCA is highlighted. The BIM approach can help in quantity estimation and analyzing the future operation and maintenance cost for LCCA with accuracy. Whereas still, data acquisition is a barrier in performing LCCA. There is a need for a BIM library that consists of the required data parameter to perform LCCA, also an LCC schema is required such as IFC and COBie to assist in data exchange for LCCA. Â© 2020 IEEE.